IMPROVING THE METABOLISABLE ENERGY VALUE OF BREWERS’ DRIED GRAINS WITH ENZYME COCKTAILS - Jimoh, Abdulhameed (Journal of Agricultural Sciences (Belgrade), 2019)
Quantification of the positive effects of exogenous enzymes is essential to ensure their inclusion in feed formulation. This study was conducted to quantify the effect of enzymes on Apparent Metabolisable Energy (AME) value of Brewers’ Dried Grains (BDG). Xylanase, phytase and multipurpose enzymes were used in a completely randomized design. There were eight treatments comprising of a control and seven experimental treatments with BDG and one or two or the three enzymes. The AME values were determined using the intubation method. Data collected were analyzed using Statistical Analysis System. Enzymes individually and as cocktail improved the AME value of BDG compared to the control. Increments in AME value are in the order 3.48%, 5.39%, 5.92%, 14.29%, 18.13%, 23.21% and 29.58% respectively for phytase, xylanase, cocktail of xylanase and phytase, multipurpose, cocktail of multipurpose and phytase, cocktail of xylanase and multipurpose and cocktail of xylanase, phytase and multipurpose. It was concluded that cocktail of enzymes is better than individual enzymes in their effects on AME of BDG.